2022
DOI: 10.3390/ijms23094482
|View full text |Cite
|
Sign up to set email alerts
|

Free Fatty Acid Receptor 4 (FFA4) Activation Ameliorates Imiquimod-Induced Psoriasis in Mice

Abstract: Dietary supplementation with n-3 polyunsaturated fatty acids (n-3 PUFA) has been used as an adjunct therapy for psoriasis due to its anti-inflammatory properties. Free fatty acid receptor 4 (FFA4 or GPR120) is a receptor-sensing n-3 PUFA. In the present study, we examined whether FFA4 acted as a therapeutic target for n-3 PUFA in psoriasis therapy. Experimentally, psoriasis-like skin lesions were induced by treatment with imiquimod for 6 consecutive days. A selective FFA4 agonist, Compound A (30 mg/kg), was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…In previous studies, pro-inflammatory cytokine productions, including Il-17, Tnf-α, Ifn-γ, Il-1β, Il-2, Il-6, Il-23, and Il-27 from immune cells such as T cells, macrophages, dendritic cells, and neutrophils have been shown to be suppressed by n-3 PUFAs [ 38 ]. The involvement of FFA4 in the CpdA-induced suppression of pro-inflammatory cytokines has been shown in allergic asthma ( Il-4 , Il-5 , Il-13 , Ifn-g , and Il-17a ), atopic dermatitis ( Il-4 , Il-13 , Ifn-g , and Il-17a ), and psoriasis ( Il-17a , Il-22 , Il-23 , Il-1b , Ifn-g , and Tnf-a ) models using Ffa4 gene KO mice [ 30 , 39 ]. In the present study, levels of the representative pro-inflammatory Th1/Th17 cytokines ( Il-1b , Tnf-a , Il-6 , and Il-17a ) in a CIA arthritis model were increased by CIA and reversed by CpdA in an Ffa4 gene-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies, pro-inflammatory cytokine productions, including Il-17, Tnf-α, Ifn-γ, Il-1β, Il-2, Il-6, Il-23, and Il-27 from immune cells such as T cells, macrophages, dendritic cells, and neutrophils have been shown to be suppressed by n-3 PUFAs [ 38 ]. The involvement of FFA4 in the CpdA-induced suppression of pro-inflammatory cytokines has been shown in allergic asthma ( Il-4 , Il-5 , Il-13 , Ifn-g , and Il-17a ), atopic dermatitis ( Il-4 , Il-13 , Ifn-g , and Il-17a ), and psoriasis ( Il-17a , Il-22 , Il-23 , Il-1b , Ifn-g , and Tnf-a ) models using Ffa4 gene KO mice [ 30 , 39 ]. In the present study, levels of the representative pro-inflammatory Th1/Th17 cytokines ( Il-1b , Tnf-a , Il-6 , and Il-17a ) in a CIA arthritis model were increased by CIA and reversed by CpdA in an Ffa4 gene-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Endogenous conversion of n-6 to n-3 PUFA in fat-1 transgenic mice restores the balance between Th17 and Treg in CIA [ 16 ]. Previously, we have demonstrated that CpdA activation of Ffa4 suppressed allergic asthma, which is driven by Th2 cytokines, and psoriasis, which is driven by Th17 cells [ 30 , 39 ]. In addition, CpdA treatment suppressed the differentiation of naïve T cells into Th17 cells in vitro and increased the Th17-cell population in a psoriasis-like animal model in an Ffa4 gene-dependent manner [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This leads to attenuation of inflammation, lower mucin secretion, reduction of both pro-inflammatory cytokines (IL-4, IL-5, IL-13, IFN-γ, and IL-17A) and number of immune cells (eosinophils and lymphocytes) in bronchoalveolar lavage fluid. 58 There are reports of omega-3 acids supplementation in mice leading to increased airway reactivity. This phenomenon is a result of interaction with sphingolipid metabolism, and is not associated with inflammation.…”
Section: Omegamentioning
confidence: 99%
“…In 3D engineered skin models replicating psoriasis conditions, the exogenous introduction of ALA led to reduced T-cell penetration into the epidermal layer, along with a notable reduction in inflammatory markers such as CXCL1, IL-6, and IL-8 ( 42 ). Moreover, the application of a targeted FFA4 agonist resulted in substantial alleviation of IMQ-triggered psoriasis-like skin aberrations and inhibited the transition of CD4+ T cells into Th17 cells ( 43 ).…”
Section: Regulation Of Lipid Metabolism On T Cell In Psoriasismentioning
confidence: 99%